Principal's Effective Communication and Teacher Performance: A Classroom Perspective - Sofia, Sofia; Syaidah, Khasnah; Shunhaji, Akhmad (Kelola: Jurnal Manajemen Pendidikan, 2023)
This research analyzes the school principal's effective communication towards improving teacher performance. Effective principal-teacher communication is essential for building trust and mutual support. This research uses qualitative methods, with a narrative research design involving five class teachers in one of the elementary schools in Cibitung Sub-District, Bekasi Regency, West Java Province. Data collection was carried out through interviews, observation and documentation studies. Inductive and thematic data analysis was conducted using NVivo 12 Plus to identify, evaluate, and create themes expressed by participants. This research shows that the principal's effective communication has an impact on the performance of classroom teachers through the principles established by the principal. This research contributes to improving effective school principal communication so that it has an impact on the quality of educational units and the findings can be used by policy makers in determining the direction of school principals in leading educational units.